The recombinant l-lysine α-oxidase from the fungus Trichoderma harzianum promotes apoptosis and necrosis of leukemia CD34 + hematopoietic cells - Costa, Mariana do Nascimento; Silva, Thiago Aparecido [UNESP]; Guimarães, Dimitrius Santiago Passos Simões Fróes; Ricci-Azevedo, Rafael; Teixeira, Felipe Roberti; Silveira, Leonardo Reis; Gomes, Marcelo Damário; Faça, Vítor Marcel; de Oliveira, Eduardo Brandt; Calado, Rodrigo T.; Silva, Roberto N. (Springer Nature, 2024)
Background: In hematologic cancers, including leukemia, cells depend on amino acids for rapid growth. Anti-metabolites that prevent their synthesis or promote their degradation are considered potential cancer treatment agents. Amino acid deprivation triggers proliferation inhibition, autophagy, and programmed cell death. l-lysine, an essential amino acid, is required for tumor growth and has been investigated for its potential as a target for cancer treatment. l-lysine α-oxidase, a flavoenzyme that degrades l-lysine, has been studied for its ability to induce apoptosis and prevent cancer cell proliferation. In this study, we describe the use of l-lysine α-oxidase (LO) from the filamentous fungus Trichoderma harzianum for cancer treatment. Results: The study identified and characterized a novel LO from T. harzianum and demonstrated that the recombinant protein (rLO) has potent and selective cytotoxic effects on leukemic cells by triggering the apoptotic cascade through mitochondrial dysfunction. Conclusions: The results support future translational studies using the recombinant LO as a potential drug for the treatment of leukemia.
Keywords: Cancer treatment; l-lysine α-oxidase; Leukemia; Trichoderma harzianum